Family-led learning through parenting in family business - Antonius Tanan; Hadi Cahyadi Ng; Jacob Donald Tan; John Lee Kean Yew (Journal of Innovation and Entrepreneurship, 2023)
This paper aims to conceptualize a family business parenting approach called family-led learning to break the third-generational curse in family business. This means that family business can hardly surpass the third generation. Family enterprises is expected to represent approximately 40 percent of the world's largest corporations by 2025, but this will not come to realization if parenting approach is not learned by the leaders of the family and experienced by the next generations. In Indonesia, family business composes around 95 percent of all the businesses and contributes about 80 percent to the country's economy. Since it is crucial to sustain the family business in Indonesia, theorizing the parenting approach for succession is vital. Applying grounded theory, this inquiry constructed the "Parenting to Equip" category in Parenting-Harmonizing-Collaborating (PHC) theory by interviewing 28 participants from four family conglomerates that are public-listed companies and are planning beyond the third generation. Next, this study integrated the Community of Inquiry (CoI) theory to the "Parenting to Equip" component to create a deep and meaningful learning experience. This results in the Family-Led Learning in Family Business (FLL-FB) concept that enable effective parenting to equip the next generations. This novel insight denotes parents of family businesses must incorporate entrepreneurial training into their parenting practices through nonformal learning experiences in informal learning environments to equip the next generations become potential successors.
Keywords: 650; Community of inquiry; Family-led learning in family business; Grounded theory; Integrating theories; Parenting-harmonizing-collaborating